KULTUR TUNAS Scoparia dulcis, lindernia anagalis, Lindernia ciliata DAN UPAYA BIOREMEDIASI TERHADAP LOGAM BERAT PB, CR, CD - Djoko Santosa; Nurma Sabila; Irma Puspita Dewi; Luthfia Nurul Aini (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
The research about shoot culture of Scoparia dulcis, Lindernia anagalis, Lindernia ciliata has beeen done. The aim of this research is to know ability of shoot culture of Scoparia dulcis, Lindernia anagalis, Lindernia ciliata to adsorb heavy-metal Pb, Cr and Cd as bioremediation process for heavy metal pollutant. Scoparia dulcis, Lindernia anagalis, and Lindernia ciliata shoots are inoculated in Murashige-Skoog (MS) semi-solid medium with added 2 ppm of kinetin as growth factor. Shoots are subcultured at 21 days then they are cultivated in MS semi-solid medium with added heavy-metal Pb, Cr and Cd during 30 days. Scoparia dulcis, Lindernia anagalis, Lindernia ciliata able to adsorb Cr but they can not adsorb Cd. Scoparia dulcis is not able to adsorb Pb.